Characterization and release profile of sodium diclofenac halal hard shell capsules made from k-carrageenan and xanthan gum with sorbitol plasticizer - Tri Susanti; Siti Wafiroh; Esti Hendradi; Pratiwi Pudjiastuti (Universitas Airlangga, 2020)
Halal hard shell capsules are importantly needed by Indonesian consumers, who are predominantly Muslim, to substitute mostly used and commercially available products made from non-halal ingredients such as gelatin. The objective of this study is to prepare, characterize, and evaluate halal hard shell capsules made from k-carrageenan-xanthan gum with sorbitol as the plasticizer with diclofenac sodium as the model drug. Hardshell capsules were prepared with combinations of κ-carrageenan-xanthan gum at a weight ratio of 4:2 with the addition of 70% sorbitol, which added at a varied volume of 0.25; 0.50; 0.75; and 1.00 mL. Characterization of halal hard shell capsules includes swelling degree, tensile strength, Fourier Transformed Infrared (FTIR) and Scanning Electron Microscope (SEM), as well as disintegration test. The diclofenac sodium profile release was evaluated through the dissolution test at pH 6.8. The best physical characteristics were obtained by preparing capsule shells with a mixture of carrageenan-xanthan gum at a weight ratio of 4:2 with the addition of 0.25 mL sorbitol. The evaluation of Halal hard shell capsules showed that it had a swelling rate of 3.46% in water media, stress modulus of 28.6 MPa, strain modulus of 4.3 MPa, and modulus young of 362,3%, as well as disintegration time of capsules, was 51.8 minutes at pH 6.8. The dissolution test showed that diclofenac sodium was released at a level of 2.7% for 16 minutes. Based on this data, it can be concluded that the Halal hard shell capsule of κ-carrageenan-xanthan gum with the addition of sorbitol can be used as an alternative for the gelatin capsule with more controlled release.